Stunting Budget Management Analysis in South Halmahera Regency - Novia Aryanti; Abdul Hadi Sirat; Hartaty Hadady (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to evaluate the effectiveness of stunting budget management in the South Halmahera Regency. A qualitative approach was employed through structured interviews with leaders of BAPPELITBANGDA, the Health Office, and three program beneficiaries. The findings indicate that the effectiveness of financial management is strongly influenced by the quality of budget planning, discipline in implementation, and transparent and accountable supervision and reporting. The budget planning process was assessed as adequate, marked by cross-sector involvement to ensure the implementation of both sensitive and specific interventions. Although the stunting budget has increased over the past three years, in 2023 only 9 out of 23 priority activities were effectively realized. The study also identifies several inhibiting factors, including limited regional budget capacity and high dependence on central government funding, suboptimal cross-sectoral coordination, and underutilization of real-time data by relevant local government agencies. Additionally, high poverty levels pose a significant challenge to efforts in accelerating stunting reduction. These findings highlight the need to strengthen budget management capacity, improve inter-sectoral coordination, and optimize the use of information technology to support data-driven decision-making.